Leveraging microcredentials for sustainability literacy in higher education: A case study of reflective thinking and learning impact in science - Brittany Lee Vermeulen; Julie M. Old; Michelle C. Moffitt; Jen Dollin (PLoS ONE, 2026)
Microcredentials are becoming increasingly popular in higher education. Despite their growing popularity, there is limited exploration of microcredentials’ potential for lifelong learning and their role in sustainability education within curricula. Furthermore, the use of and evaluation of reflective thinking linked to science and sustainability within these online offerings is unexplored. Undertaken in 2024, a large undergraduate science subject, Complex Case Studies in Science (n = 435), embedded a short microcredential titled ‘Sustain ability : Think, Care, Do’ to foster sustainability learning outcomes. The microcredential introduces learners to key concepts of sustainability, understanding diverse worldviews, unpacking their values and how to think systemically, as well as the relevance of these literacies to their science discipline. Our paper explores the learning of a participating cohort of undergraduate students (n = 33) in developing sustainability literacies through this online intervention to culminate in a final reflective assessment of the subject. Using reflexive thematic analysis, we analysed the students’ reflective assessment task. Our findings demonstrate how an online microcredential enhanced science students’ understanding of sustainability, re-evaluation of their daily practices and professional identities, and the development of literacies that grapple with complexity and interdisciplinary solutions across sustainability domains. We also quantified their engagement through behavioural analytics, which varied greatly as expected with an independent self-paced online course. We share these insights as a blueprint for higher education practitioners to integrate online sustainability microcredentials into their curricula at scale.